The Implementation of School Literacy Movement by Using Storybook in Elementary School - Wahab, Isnaeni; Amaliyah, Nurhadifah (International Journal of Elementary Education, 2021)
Literacy is one way to build and develop children's thinking skills that are important for students. However, students' literacy habits are still low. Therefore, schools as one of the three educational centers should implement a literacy culture to improve children's thinking skills. This study aims to examine information about the application of literacy culture in schools and to apply literacy using children's stories for students. This study uses a qualitative descriptive approach with a survey method. The subjects of this study were elementary school students. Data collection techniques through observation, interviews, and documentation. Data analysis through the stages of data reduction, data presentation, and concluding. The results showed that literacy activities in schools had been implemented with literacy fifteen minutes before the lesson started and used every corner of the school as a reading corner, while the implementation of literacy using storybooks was done by inviting students to read books with various story titles. Based on these results, it can be concluded that elementary schools already have a good literacy program and the application of literacy using storybooks can invite students to retell the story content and the moral values of the story. This research implies that schools should optimize their role as one of the three educational centers to build and develop literacy habits for elementary school students.